KAJIAN APLIKASI HADIS DI GOOGLE PLAY STORE (Telaah Aplikasi ‘Katalog Hadis Palsu & Tiada Asal’ Karya Fariz Abdul Azziz) - Hidayah, Saniatul; Robby Habiba Abror (Al-Bayan: Journal of Hadith Studies, 2025)
The study of hadith has developed very rapidly. This is characterized by the existence of applications or software that can facilitate and support the study of hadith. So that the application must be developed in such a way that it can be attracted and used by the wider community. One of these applications is the 'Catalog of False & Original Hadith' developed by Fariz Abdul Azziz. This research falls into the category of qualitative research because it includes research on literature. This study will examine the 'Catalog of False & Original Hadith' application, starting from the background of its development, the various features of this application, the pattern of presentation of hadith as well as the advantages and disadvantages of the 'Catalog of False & Original Hadith' application. This application can be found on Google Play Store and can be downloaded for free on smartphones so that it can be used in various places and can be used at any time. This application contains traditions that are considered false/maudhu' and are presented in different themes. The presentation pattern is very interesting. The themes are organized in a structured manner and serve as a practical guide for the users of the app to get to know the various traditions that are considered false/maudhu'. More interestingly, the content in this application is presented in Malay. However, this does not diminish the essence of this application to recognize various false traditions. With this application, it can provide convenience for people at all levels in learning about false traditions.